PENGARUH ASSET GROWTH DAN REVENUE GROWTH TERHADAP RETURN ON ASSETS (ROA) PADA PT ALAMTRI RESOURCES INDONESIA TBK PERIODE 2015-2024 - Safitri, Arinda Dwi; Fikron Al-Choir (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of Asset Growth and Revenue Growth on Return on Assets (ROA) at PT Alamtri Resources Indonesia Tbk during the period 2015–2024. This research employs a quantitative method using multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) processed with IBM SPSS Statistics 27. The results show that partially Asset Growth has a t-value of 0.871 with a significance value of 0.417 (>0.05), indicating no significant effect on ROA. Likewise, Revenue Growth has a t-value of 2.184 with a significance value of 0.072 (>0.05), which also indicates no significant effect on ROA. Simultaneously, Asset Growth and Revenue Growth do not have a significant effect on ROA, as indicated by an F-value of 2.387 with a significance level of 0.173 (>0.05). The Adjusted R Square value of 0.257 indicates that 25.7% of the variation in ROA can be explained by Asset Growth and Revenue Growth, while the remaining 74.3% is influenced by other factors outside the research model.